Analisis Partisipasi Forum Anak sebagai Pelopor dan Pelapor dalam Mewujudkan Kota Layak Anak (KLA) di Kabupaten Pandeglang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role of the Forum Anak (Children's Forum) in Pandeglang Regency in realizing a Child-Friendly City (KLA), with a focus on the implementation of the 2P functions (Pioneer and Reporter) in the participatory process. The Forum Anak is designed as a channel for conveying children’s aspirations to the government, in line with Regional Regulation No. 1 of 2021 of Pandeglang Regency. The results of the study show that the Forum Anak of Pandeglang Regency has actively involved children in various programs and activities, such as capacity-building training and public consultation forums. However, challenges remain in spreading knowledge about children's rights and expanding the involvement of Forum Anak across all areas of the regency. Overall, the participation of Forum Anak is categorized at the